Fretting wear behaviour of biomedical grade Ti6Al4V produced by electron beam powder bed fusion - Soria, Sergio Raul; Soul, Hugo Ramon; Bergant, Marcos Antonio; Yawny, Alejandro Andres (Elsevier, 2024)
Fil: Soria, Sergio Raul. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina